GIS cartography. A guide to effective map design (third edition) - Włodarski, Wojciech (Geologos, 2024)
Book review: GIS cartography. A guide to effective map design (third edition), by Gretchen N. Pethersen, 2021. CRC Press Taylor & Francis Group, Boca Raton/London; 318 pages, Price £31.99, ISBN 978-0-367-85794-3.